TOWARDS TECHNOLOGICAL AWARENESS AND WISDOM - van Wyk, Rias Johann (The South African Journal of Industrial Engineering, 2020)
This article aims to enhance technology foresight by contributing to technological awareness and wisdom. It is based on an understanding of the fundamental nature of technology, and requires an overarching view. This needs at least three constituents: (1) a universal definition of technology; (2) a central organising framework; and (3) a methodology for measuring technological advance at the national level. The article then addresses these constituents. It examines the status of each and projects what needs to be done.